The contributing factor to the smoking habit among students: a case study at Tun Mamat College, Melaka / Amar Martin Rahimi and Mohamad Shafrien Sam - Rahimi, Amar Martin; Sam, Mohamad Shafrien (Faculty of Administrative Science and Policy Studies, 2012)
Smoking is considered the main avoidable cause of death and the most important public health risk. The hazards of tobacco affect not only smokers, but also non-smokers who are exposed to cigarette smoke. In this study, the researchers are focus on the contributing factors to the smoking habit among the students. The purpose of this study is to examine how environment lead to the smoking habit among students, to examine whether social factor lead to the smoking habit among students, to determine whether psychology influence to the smoking habit among students, to identify whether people addiction influence to the smoking habit among students and to examine the most influence factor that lead to smoking habit. For this study, a convenience sampling technique was used and the target respondent is the Tun Mamat college student itself. The sample size of this study is 127 students and consists of students from various parts and also consists of students from various faculties. Based on finding, the correlation analysis shows that all the variables shows positively significant relationship with the dependent variable which is the perception on the smoking habit among students. While multiple regression indicates that all the variables is significantly influential in relation to the contributing factors to the smoking habit among students. However, the finding indicates that people addiction is the most contribution factor lead smoking habit and it have a positive relationship with smoking habit when (r = .616, p > .05.